1955
DOI: 10.1104/pp.30.6.504
|View full text |Cite
|
Sign up to set email alerts
|

Transient Changes in Cellular Gas Exchange and the Problem of Maximum Efficiency of Photosynthesis

Abstract: PLANT PHYSIOLOGY P32 labeled compounds of the xylem exudate. Only radioactive inorganic sulfate was present on chromatograms of the exudate collected over 24 hours. The S35 inorganic sulfate in the exudate fluid was isolated chromatographically as easily as the phosphate, but no detailed study of time versus amount of S35 in the exudlate has been run. SUMMARYThe xylem exudate of several species of plants contained three P32 labeled compounds-inorganic phosphate, and two unknown phosphorus containing compounds.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

1957
1957
1992
1992

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(13 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…One concept, espoused by Warburg et al (3), was that photosynthetic quantum conversion has an efficiency of about 90%-i.e., that energy equivalent to that of 3 einsteins of red quanta (42 kcal each) is sufficient to liberate 1 mol of 02 (corresponding to 1/6 mol of glucose, for which AGO' = 686/6 = 114 kcal). In contrast, Emerson (4) and his followers (5) concluded that photosynthetic efficiency was much lower, of the order of 8 to 12 quanta per 02, a range that is widely accepted today even though values less than 8 have, at times, been obtained by investigators (6,7) who did not share Warburg's conclusions.…”
mentioning
confidence: 82%
See 1 more Smart Citation
“…One concept, espoused by Warburg et al (3), was that photosynthetic quantum conversion has an efficiency of about 90%-i.e., that energy equivalent to that of 3 einsteins of red quanta (42 kcal each) is sufficient to liberate 1 mol of 02 (corresponding to 1/6 mol of glucose, for which AGO' = 686/6 = 114 kcal). In contrast, Emerson (4) and his followers (5) concluded that photosynthetic efficiency was much lower, of the order of 8 to 12 quanta per 02, a range that is widely accepted today even though values less than 8 have, at times, been obtained by investigators (6,7) who did not share Warburg's conclusions.…”
mentioning
confidence: 82%
“…Using the total number of quanta absorbed by both cyclic and noncyclic photophosphorylation, we calculated a requirement of about 6 quanta per NADPH for chloroplasts from young plants and about 8 quanta for chloroplasts from old plants (Table 3).…”
mentioning
confidence: 99%
“…That much is not in doubt but the world of photosynthesis agonized for years over the question of how many photochemical events combine to bring about tbe fixation of one molecule of CO^, tbe liberation of one molecule of oxygen. The German Nobel Laureate, Otto Warburg (Warburg & Negelein, 1923;W'arburg & Burk, 1950;Warburg, Geleick & Briese, 1952;Warburg, 1958;W'arburg, Krippahl & Lehman, 1969), said 4 (or even less), bis erstwhile American student, Robert Emerson, said at least 8, possibly 12 (Emerson & Green, 1938;Emerson & Lewis, 1939, 1941, 1943Emerson & Chalmers, 1955;Emerson, 1958;Kok, 1960;Radmer & Kok, 1977). The debate was passionate, even bitter.…”
Section: Historicalmentioning
confidence: 99%
“…Short-term manometric techniques used by Warburg were severely criticized by Emerson and co-workers because of transients in COg and O^ exchange associated with light-dark transitions (the so-called bursts). On the basis of these artifacts, as elaborated by Emerson (Emerson & Chalmers, 1955;Emerson, 1958), much of the other experimental work where this was thought to be a problem has been discredited. The two vessel manometric technique used by Warburg in other studies (Warburg & Bruk, 1950) was not prone to these errors, nor were gas exchange transients a problem in those experiments conducted over long time intervals.…”
Section: Iscussionmentioning
confidence: 99%
“…Both investigations show widely diverging values of the measured photon requirement which varies in conjunction with changes in the gas exchange quotient (COg flux divided by the Og flux). In order to avoid confusing experimental observations, which may have been made under suboptimal conditions, with the true minimum photon requirement, we will call the measured values apparent photon requirements (^co o) ^^ distinguish them from the true minimum value (^cog ^^ Og)-This formality is necessary because much of the controversy over the correct value of the minimum photon requirement has been exacerbated by questions regarding methodological problems and the interpretation of results (Nishimura, Whittingham & Emerson, 1951;Kok, 1952Kok, , 1960Emerson & Chalmers, 1955) and because the reactant (i.e. COg) and product (i.e.…”
Section: Introductionmentioning
confidence: 99%